2018
DOI: 10.1177/0748233717754163
|View full text |Cite
|
Sign up to set email alerts
|

Lead induced oxidative DNA damage in battery-recycling child workers from Bangladesh

Abstract: Lead exposure can damage cells directly by effecting DNA or indirectly by modifying proteins and enzymes. In Bangladesh, many working children are exposed to a very high level of lead during their early life due to their involvement with lead-oriented professions. This imposes a severe threat to the growth and development of the children. Therefore to study the effect of lead, we enrolled 60 age-matched male children, from an area of old Dhaka city, where battery-recycling shops are located, depending on their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Three papers assessed oxidative stress and DNA damage caused by lead exposure [69] or a combination of metals [14,59]. All three reported significantly altered oxidative stress parameters in exposed groups, with two [14,69] reporting increased DNA damage.…”
Section: Metals and Health Outcomes (N = 13)mentioning
confidence: 99%
See 2 more Smart Citations
“…Three papers assessed oxidative stress and DNA damage caused by lead exposure [69] or a combination of metals [14,59]. All three reported significantly altered oxidative stress parameters in exposed groups, with two [14,69] reporting increased DNA damage.…”
Section: Metals and Health Outcomes (N = 13)mentioning
confidence: 99%
“…Three papers assessed oxidative stress and DNA damage caused by lead exposure [69] or a combination of metals [14,59]. All three reported significantly altered oxidative stress parameters in exposed groups, with two [14,69] reporting increased DNA damage. Specifically, Lahiry et al's low quality paper stated that one marker of DNA damage was 15.6 times higher in the exposed group, although limitations in study methodology must be considered [14].…”
Section: Metals and Health Outcomes (N = 13)mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the displacement of particulate matter from air into the aqueous phase, Pb solubilization in lung fluid may result in absorption into the blood via the air–blood barrier . Solubilized transition metals may cause localized pulmonary toxicity, translocate to extra-pulmonary organs (e.g., heart and liver), and exert systemic toxicity (e.g., DNA and hepatic damage by oxidative stress). …”
Section: Introductionmentioning
confidence: 99%
“…8 Solubilized transition metals may cause localized pulmonary toxicity, 10 translocate to extra-pulmonary organs (e.g., heart and liver), 11 and exert systemic toxicity (e.g., DNA and hepatic damage by oxidative stress). 12 Unlike the ingestion pathway, where Pb absorption may be influenced by the nutritional status (i.e., fed vs unfed, cations, and lipid composition of diet), 15,16 a higher fraction of solubilized Pb may be absorbed in the lungs because of the high surface area and extensive vascularization of the respiratory system, coupled with the short air−blood barrier separation. 17 Inhalation studies in humans using Pb particles (<1 μm) have reported that up 95% of Pb deposited in the lungs was absorbed, 18,19 with a half-life of 0.8−44 h in the blood, 20 while ultrafine particles (<100 nm) may be immediately absorbed (e.g., Pb fumes).…”
Section: ■ Introductionmentioning
confidence: 99%